Multifrequency Subpulse SAR: Exploiting Chirp Bandwidth for an Increased Coverage - Bordoni, Federica; Krieger, Gerhard; Younis, Marwan (IEEE Geoscience and Remote Sensing Letters, 2018)
Spatial resolution and swath width are fundamental quality parameters for spaceborne synthetic aperture radar (SAR) products. They have driven the research on new spaceborne SAR system concepts in the last decades, and a new generation of SAR systems is emerging. Main feature of these future systems is the use of multiple digital channels and new SAR processing techniques. A further characteristic is that they can resort to a large radar signal bandwidth. In this paper, a novel SAR operational mode is presented, denoted as multifrequency subpulse (MFSP). The MFSP exploits the available radar signal bandwidth to increase the imaged swath extension, without the emergence of range ambiguities. The proposed approach is explained both theoretically and by a design example, based on the future German X-band SAR system, High-Resolution Wide-Swath (HRWS). Moreover, the achievable SAR imaging quality is investigated.
Keywords: High-resolution wide-swath (HRWS); multichannel synthetic aperture radar (SAR); digital beamforming (DBF).